Gomez-Lopez-Hernandez Syndrome: Expanded Phenotype - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Since the first patient with cerebello-trigeminal-dermal dysplasia, later called Gomez-Lopez-Hernandez syndrome, was reported in 1979 by Gomez et al, six more cases have been added to the literature.